Inexpensive monolithic additive manufacturing of silicone structures for bio-inspired soft robotic systems. (1st March 2023) - Ovy, S M Al Islam; Stano, Gianni; Percoco, Gianluca; Cianchetti, Matteo; Tadesse, Yonas
Abstract: In soft robotics, the fabrication of extremely soft structures capable of performing bio-inspired complex motion is a challenging task. In this paper, an innovative 3D printing of soft silicone structures with embedded shape memory alloy (SMA) actuators are proposed, which is completed in a single printing cycle from CAD files. The proposed custom-made 3D printing setup, based on the material extrusion (MEX) method, was used in conjunction with a cartesian pick and place robot (CPPR) to completely automate the fabrication of thick silicone skins (7 mm) with embedded shape memory alloy actuators. These structures were fabricated monolithically without any assembly tasks and direct human intervention. Taking advantage of the capability to 3D print different geometries, three different patterns were fabricated over the silicone skin, resulting in remarkable dynamic motions: an out-of-plane deformation (jumping of the structure from the x-y plane to the x-z plane) was achieved for the first-time employing silicone skin, to the best of the author's knowledge. In addition, two process parameters (printing speed and build plate temperature) and the extruded silicone curing mechanisms were investigated to enhance the printing quality. This paper aims to advance the role of additive manufacturing in the field of soft robotics by demonstrating all the benefits that a low-cost, custom-made silicone 3D printer can bring to the table in terms of manufacturing soft bio-inspired structures.